PENDEKATAN BPMN DALAM MEMBUAT ABSTRAKSI PROSES BISNIS PENGELOLAAN PENELITIAN DI UNIVERSITAS SILIWANGI - Irani Hoeronis (Informatics Engineering Department of Halu Oleo University, 2018)
Research is one of the higher education dharma which is the leading business in Siliwangi University. The primary business abstraction process at Siliwangi University became important in assisting the implementation of Tridharma, especially the management of the research. In addition to the primary business abstraction process, simulation is also needed to clearly see the role of each part in the development of the quality and quantity of research.This study aims to model the development of the quality and quantity of research using the BPMN approach. From the BPMN simulation results, currently, (as-is) Siliwangi University shows a balanced role between LP2M-PMP, Academic Bureau, and Rectorate. To maximize the role of each part, this research creates a scenario by targeting the implementation of the development of the quality and quantity of research in a period of 6 months from the scenario simulation results, it can be seen that the role of the Academic Bureau dominates by 71.85% compared to the Rectorate by 63.08% and LP2M-PMP by 50.97%.Keywords—Development of Quality and Quantity of Research, Business Processes, BPMN.DOI: 10.5281/zenodo.1471134